Divine Play in Vṛndāvan: An Exploration of Śrī Kṛṣṇa Līlā in the Śrimad Bhāgavata Mahāpurāṇa - Pokhrel, Mohan Kumar (JODEM: Journal of Language and Literature, 2024)
The Śrimad Bhāgavata Mahāpurāṇa, a cornerstone of Hindu scripture, intricately weaves together a tapestry of divine narratives relating to Śrī Kṛṣṇa līlā. The Kṛṣṇa līlā unfolds a kaleidoscope of enchanting episodes from the life of Śrī Kṛṣṇa, the eighth incarnation of Lord Vishnu, revered as the supreme embodiment of divine love and wisdom. The Śrimad Bhāgavata Mahāpurāṇa intricately portrays Krishna’s multifaceted persona, showcasing his roles as a compassionate friend, a fearless protector, and a profound philosopher. It delves into his divine interventions, such as the lifting of Mount Govardhan to shelter the residents of Vṛndāvan from Indra’s wrath, and his legendary Rāsalīlā, a celestial dance of divine love with the Gopīs, symbolizing the union of the individual soul with the Supreme. The major objects of this study are to explore Śrī Kṛṣṇa līlā in the Śrimad Bhāgavata Mahāpurāṇa; to examine Śrī Kṛṣṇa līlā for our understanding of the philosophical concepts of the divine play in the text; and to evaluate Śrī Kṛṣṇa līlā in the Śrimad Bhāgavata Mahāpurāṇa. For the analysis of the primary text, the researcher has used Sanātana Gosvāmī’s principle of līlā. The theorist claims that humans perform different activities as līlā in their lives. The interpretative method has been used in the analysis of this article. The result drawn from this investigation is Śrī Kṛṣṇa līlā in the Śrimad Bhāgavata Mahāpurāṇa serves as a timeless reservoir of spiritual wisdom and awakens to the eternal truths of love, devotion, and self-realization. The discussion concludes that the portrayal of Śrī Kṛṣṇa līlā in the Śrimad Bhāgavata Mahāpurāṇa stands as a pinnacle of devotional literature, encapsulating the essence of divine play, love, and wisdom.